PENGEMBANGAN MEDIA KARTU BILANGAN BERBASIS MATH GAMES DENGAN PENDEKATAN PMRI PADA MATERI PENJUMLAHAN BERSUSUN KELAS II SD - Rino Wijayanti; Jayanti; Ida Suryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop valid and practical math games-based number card media with the PMRI approach on compound addition material for grade II of SD Negeri Ringin Agung. This study uses the R&D method found in the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation. The instruments in this study used questionnaires and documentation. The questionnaire was presented to validators of material, media, language, teachers and students while the results of one to one were 4 students and small groups of 15 students of grade II of SD Negeri Ringin Agung. The results of validation by material experts on number card media based on math games obtained a score with a percentage of 94%, including the "very valid" criteria. The results of validation by media were obtained by a score with a percentage of 80% included in the "Very Valid" criteria. The results of validation by language were obtained by a score with a percentage of 83% included in the "Very Valid" criteria. The results of three validations of number card media based on math games obtained a score with an overall of 80%, included in the "Very Valid" criteria. While the results from the teacher were 90%, included in the "Very Eligible" criteria. The results of one to one were 88.12% and small group were 88.33% included in the "Very Eligible" criteria.